2010
DOI: 10.1037/a0018590
|View full text |Cite
|
Sign up to set email alerts
|

Graphing the order of the sexes: Constructing, recalling, interpreting, and putting the self in gender difference graphs.

Abstract: Published as Hegarty, P., Lemieux, A., & McQueen, G. (2010). Graphing the order of the sexes: Constructing, recalling, interpreting, and putting the self in gender difference graphs. Journal of Personality and Social Psychology, 98,[375][376][377][378][379][380][381][382][383][384][385][386][387][388][389][390][391]. AbstractGraphs seem to connote facts more than words or tables do. Consequently, they seem unlikely places to spot implicit sexism at work. Yet, in 6 studies (N _ 741), women and men constructed (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 113 publications
(169 reference statements)
1
44
0
1
Order By: Relevance
“…Again, it is likely that lower‐status groups define themselves as different, but for different motivations than higher‐status groups. Whilst our work on linguistic framing has found little evidence of effects of group identity on explanation content, there are suggestive findings that people engage with science in ways that are affected by social identity concerns (e.g., Hegarty, Lemieux, & McQueen, 2010; Morton, Haslam, Postmes, & Ryan, 2006). More work is needed on this question of how the focus of attention might shift when people explain group differences as individuals, and when they explain group differences as members of higher‐ and lower‐status social groups.…”
Section: Future Directionsmentioning
confidence: 71%
“…Again, it is likely that lower‐status groups define themselves as different, but for different motivations than higher‐status groups. Whilst our work on linguistic framing has found little evidence of effects of group identity on explanation content, there are suggestive findings that people engage with science in ways that are affected by social identity concerns (e.g., Hegarty, Lemieux, & McQueen, 2010; Morton, Haslam, Postmes, & Ryan, 2006). More work is needed on this question of how the focus of attention might shift when people explain group differences as individuals, and when they explain group differences as members of higher‐ and lower‐status social groups.…”
Section: Future Directionsmentioning
confidence: 71%
“…Indeed, studies across a number of domains have shown that people are less mindful of more prototypical social groups, and particularly so when such groups are of high-status (Hegarty, Lemieux, & McQueen, 2010). For instance, research in social cognition has demonstrated that individuals asked to categorize others by race are slower to do so for White targets-the more prototypical group-than they are for Black targets (Richeson & Trawalter, 2005;Stroessner, 1996).…”
Section: Proposition 2: Homogeneity Is Also An Effect In Need Of Explmentioning
confidence: 99%
“…Across the front of the cover we see a sequence of images, made up of various combinations of the standard male ♂ and female ♀ symbols. Hegarty, Lemieux and McQueen (2010) have found that the ordering of gender and sexuality in psychological graphs and diagrams reflects dominant cultural hierarchies of acceptability and normality, with data from men generally presented before that of women, and from heterosexuals before that of bisexual, lesbian or gay (BLG) people. This is reflected in this cover which first (left to right) presents an interlocked male and female symbol, presumably representing heterosexuality.…”
Section: The Book and Its Covermentioning
confidence: 99%
“…We consider the ways in which this is inherent in both the structure and content of the book (see Hegarty, Lemieux & McQueen, 2010). We asked questions throughout the analysis such as: How are gender and sexuality represented (both visually and textually)?…”
Section: Analysing the Textmentioning
confidence: 99%